Intelligent IoT Wind Emulation System Based on Real-Time Data Fetching Approach - R. Raja Singh; Swapnil Banerjee; R. Manikandan; Ketan Kotecha; V. Indragandhi; Subramaniyaswamy Vairavasundaram (IEEE Access, 2022)
The fundamental challenge for the development of the wind energy conversion system is the natural instability of this resource, which is now at the forefront of the debate. The Internet of Things (IoT) has emerged as a smart and practical approach to renewable energy system management. In addition, the Internet of Things is an important study area with several possibilities for advancement and demanding work. To improve the dependability of wind energy conversion systems, researchers may simulate all potential wind turbine operating scenarios and design power electronics topologies and control algorithms appropriately. The proposed wind emulation platform is wind-turbine-oriented, with significantly increased traceability and efficiency when compared to existing systems. The wind emulation system is driven with real-time wind velocity data. The real-time and forecasted wind data is fetched from global nodes using an IoT cloud application programming interface. The wind emulation system is modeled in the VEE Pro platform and integrated with IoT cloud API and FPGA controller. Data obtained from IoT is converted into actionable information to analyze and investigate wind turbine performance. Also, effective security measures have been taken for ESP8266 communication with the Host Computer. Adapting the proposed IoT algorithm with an associated hardware prototype, the condition of the wind energy conversion system and the power generation capability shall be analyzed in a real-time environment.